SOCIAL MEDIA ADDICTION AND ONLINE IMPRESSION MANAGEMENT IN YOUNG ADULTS - Sareen, Shivangi; Jain, Prashasti (The journal of contemporary issues in business and government, 2022)
In the last decade social media has become immensely popular worldwide. It is a way of connecting with family and friends through sharing messages, photos and videos. As time moved forward, social media become a big part of our lives. The addiction of social media is a form of internet addiction which consists of all the features of other addiction disorders. This study aims to understand the relationship between social media addiction and impression management online among young adults. People in the online world present themselves in a manner which seems very desirable to other users which is known as online impression management. In order to maintain this impression online, a user constantly engages in being active on social media which results in high usage of social media. Data was collected using online survey method. A total of 220 people participated in the study out of which 131 participants were female and 89 participants were male. The age range of the participants was between 18 to 35 years. A regression analysis was conducted and a significant positive relationship was found between the variables. Online impression management was found to be a good predictor of social media addiction.